A cross-sectional study investigating the relationship between handgrip strength with multimorbidity in Korean adults: Findings from the Korea National Health and Nutrition Examination Survey VI-VII (2014–2017) - Lee, Mee-Ri (Medicine (Baltimore), 2021)
To date research investigating the associations between handgrip strength and multimorbidity when stratifying by age and sex is limited. Furthermore, this is the first study in a Korean population, and the first to include adults ≥ 19 years of age. Here we investigated the associations between handgrip strength and multimorbidity in Korean adults aged ≥ 19 years. In this cross-sectional study data from the Korean National Health and Nutrition Examination Survey were used. Multimorbidity was defined as having 2 or more chronic diseases. A total of 19,779 participants were eligible for the study (8730 male and 11,049 female). We grouped and analysed participants based on age and sex (men and women aged 19–49 years, men and women aged 50–80 years) and examined the associations between handgrip strength and multimorbidity using multivariate logistic regressions using stratification by age, sex and body mass index (BMI). Multivariate logistic regressions revealed a significant inverse association irrespective of sex, between relative handgrip strength and multimorbidity. Participants with the lowest handgrip strength had a significantly higher odds ratio (OR) of multimorbidity (men aged 19–49 years: 3.76 and aged 50 years to 80 years: 2.11; women aged 19 years to 49 years: 1.52 and aged 50–80 years: 2.15) when compared to those with highest handgrip strength after adjusting for confounding variables. The highest OR was observed in men aged 19 years to 49 years with a BMI ≥ 25 kg/m(2). In the current study we observed a significant inverse relationship between handgrip strength and multimorbidity in males and females with 2 or more chronic diseases. Male participants with a low handgrip strength aged between 19 years to 49 years with a BMI ≥25 kg/m(2) may be at greater risk of multimorbidity. This study highlights the need for further longitudinal studies to investigate the effects of increasing handgrip strength combined with weight loss, as an effective strategy to reduce the incidence of multimorbidity.